E-033 SOFIA Plus Distal Access Catheter for Acute Stroke Intervention-Initial Single Center Experience. (29th July 2016) - Cerejo, R; John, S; Bauer, A; Toth, G; Bain, M; Elgabaly, M; Masaryk, T; Rasmussen, P; Hussain, M
Abstract : Introduction: Endovascular thrombectomy (EVT) for acute ischemic stroke (AIS) has Level 1 evidence for improved patient outcomes compared with standard care. Effective and timely recanalization is of paramount importance to achieve this. The SOFIA Plus distal access catheter (Microvention, Tustin CA) is a newly available large lumen catheter (distal inner diameter – 0.070 inch). We present our initial experience with this device for thrombectomy in acute AIS. Methods: Retrospective analysis of all patients at our center who underwent EVT for AIS using the SOFIA Plus catheter was performed. Demographic, clinical and imaging data, and early follow-up outcomes were analyzed. Results: Nine patients underwent EVT using the SOFIA Plus catheter including 6 males with a median age of 63, and a median initial NIHSS of 18. Location of the large vessel occlusion were as follows: ICA terminus – 3, M1 segment – 4, M2 segment – 1, Basilar – 1. Primary direct aspiration method with the SOFIA Plus catheter was utilized in 7 cases, of which 3 required the use of a stent retriever in subsequent passes. In 2 cases, primary stent retriever plus aspiration via the SOFIA plus catheter technique was used. Median groin puncture to recanalization time was 33 minutes with median first pass to recanalization time of 9 minutes. TICI 2 b-3 recanalization was achieved in 8/9 cases with a median of 2 passes. None of the patients suffered a symptomatic intracranial hemorrhage. Amongst patients in whom follow up data was available, median discharge NIHSS was 4. Conclusion: In our single center experience, the SOFIA plus catheter was technically feasible, safe to use, and achieved high recanalization rates in a timely manner. Disclosures: R. Cerejo: None. S. John: None. A. Bauer: None. G. Toth: None. M. Bain: None. M. Elgabaly: None. T. Masaryk: None. P. Rasmussen: None. M. Hussain: None.